The Delivery Option on Forward Contracts - Livingston, Miles (Journal of Financial and Quantitative Analysis, 1987)
Many futures contracts contain a delivery option, which allows the short position a choice to deliver one of several varieties of a commodity. Several authors have argued that delivery options can have considerable value. For a forward contract with a delivery option, this paper shows that a continuously adjusted hedge will drive the value of the delivery option towards zero, assuming perfect and frictionless markets.